The magnitude of blood lactate increases from high speed workouts - Caruso, J. F.; Kucera, S.; Jackson, T.; Hari, P.; Olson, N.; McLagan, J.; Taylor, S. T.; Shepherd, C. (International Journal of Sports Medicine, 2011)
To examine blood lactate concentrations from high-speed exercise resistive exercise, subjects performed workouts on an inertial kinetic exercise (Oconomowoc, WI) device. Workouts entailed two 60-s sets of elbow flexor (curling) repetitions. Pre- and post-exercise blood lactate concentrations were measured, via a fingertip blood drop, with an analyzer. From workouts the average acceleration, maximum force and total torque were derived. Blood lactate concentrations were analyzed with a 2 (gender)×2 (time) ANOVA, with repeated measures for time. Average acceleration, maximum force and total torque were analyzed with one-way (gender) ANOVAs. With an ?=0.05, blood lactate concentrations had a time (pre<post) effect, while exercise performance variables had gender (men>women) effects. Current blood lactate concentrations were commensurate with other studies that used a modest level of resistance and engaged a small muscle mass. Given the current workout protocol and muscle mass engaged, as well as parallels to other results, our study appears to offer a valid portrayal of subsequent changes in blood lactate concentrations from high-speed resistive exercise.